Glacier Mass Balance Based on Two Digital Elevation Models and Ground Observation Records for the Baishui River Glacier No. 1 in Yulong Snow Mountain, Southeastern Qinghai–Tibet Plateau - Chen, Lihua; Che, Yanjun; Cao, Yun; Wang, Shijin; Ma, Xinggang (Frontiers in Earth Science, 2022)
Glacier mass balance is a key idea in understanding the relationship between glacier and climate. In this study, Landsat images, Shuttle Radar Topography Mission and Advance Land Operation Satellite digital elevation models, and ground observation records for 2000–2010 and 2019–2020 were used to analyze a mass balance of the Baishui River Glacier No. 1 (BRG1) in Yulong Snow Mountain, southeastern Qinghai–Tibet Plateau. Both glaciological and geodetic methods were used to understand the spatial pattern of the mass balance. A mass balance contour line map of the glacier was created for the first time. From 2000 to 2010, the mean annual mass balance of BRG1 was calculated to be −0.99 m w.e., −1.01 m w.e., and −1.18 m w.e. using the contour line, profile curve, and geodetic methods, respectively. In addition, the analysis revealed that strong melting of the glacier occurred from July 27 to September 15, 2019, with an averaged glacier mass balance of −1.75 m w.e. and a mean daily melting rate of 35 mm w.e. The annual mass balance was assessed to be −1.31 m w.e. during 2019/20 using the contour line method. In addition, the spatial patterns on the mass-balance contour maps for 2000–2010 and the summer of 2019, and the climate change in this region were analyzed. The results indicate that the increased air temperature was the main cause of the accelerated glacier melting.